Superprotonic Conductivity of a UiO-66 Framework Functionalized with Sulfonic Acid Groups by Facile Postsynthetic Oxidation - Phang, Won Ju; Jo, Hyuna; Lee, Woo Ram; Song, Jeong Hwa; Yoo, Kicheon; Kim, BongSoo; Hong, Chang Seop (John Wiley & Sons Ltd., 2015)
Facile postsynthetic oxidation of the thiol-laced UiO-66-type framework UiO-66(SH)(2) enabled the generation of UiO-66(SO3H)(2) with sulfonic acid groups covalently linked to the backbone of the system. The oxidized material exhibited a superprotonic conductivity of 8.4 x 10(-2) S cm(-1) at 80 degrees C and 90% relative humidity, and long-term stability of the conductivity was observed. This level of conductivity exceeds that of any proton-conducting MOF reported to date and is equivalent to the conductivity of the most effective known electrolyte, Nafion.